2001
DOI: 10.1161/01.atv.21.3.394
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Probucol in Lecithin-Cholesterol Acyltransferase–Deficient Mice

Abstract: Abstract-Cellular cholesterol release takes place by at least 2 distinct mechanisms: the lecithin-cholesterol acyltransferase (LCAT)-driven net efflux by cholesterol diffusion and the generation of high density lipoprotein (HDL) with cellular cholesterol and phospholipid on the cell-apolipoprotein interaction. Therefore, LCAT deficiency impairs the former pathway, and the latter can be inhibited by probucol, which interferes with the apolipoprotein-cell interaction. Hence, probucol was given to the LCAT-defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Probucol also protects against adriamycin-induced heart failure (60). Unfortunately, the detailed molecular mechanisms underlying probucol's diverse activities are not well understood (25)(26)(27)61). Probucol's striking effects on cholesterol metabolism (UC͞TC ratio) and lipoprotein morphology were likely to have played a key role in its cardioprotective effects and may help uncover its mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…Probucol also protects against adriamycin-induced heart failure (60). Unfortunately, the detailed molecular mechanisms underlying probucol's diverse activities are not well understood (25)(26)(27)61). Probucol's striking effects on cholesterol metabolism (UC͞TC ratio) and lipoprotein morphology were likely to have played a key role in its cardioprotective effects and may help uncover its mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…Probucol inhibited the production of HDL in mice, and the kinetic analysis of plasma HDL revealed the enhanced clearance of HDL apoprotein by probucol but no difference in the HDL-lipid clearance (24), an exact analogy to the behavior of HDL in Tangier disease patients (47), indicating that probucol inhibits the reaction to generate HDL that is lacking in patients with Tangier disease. The use of probucol in the lecithin:cholesterol acyltransferase-deficient mice showed that cholesterol accumulated only in the liver, suggesting that the liver is the major organ where generation of HDL by this mechanism takes place (48). ABCA1 was identified as a protein essentially responsible for this reaction, and the action of probucol on ABCA1 has become a subject of study.…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblasts from patients with a genetic defect of plasma HDL lack the interaction with apolipoprotein, indicating that this reaction is a main source of plasma HDL (5,6). This view is supported by the finding that probucol, which markedly reduces plasma HDL, blocks the cell-apolipoprotein interaction (7)(8)(9). Mutations were identified in ATP-binding cassette transporter (ABC) A1 with many HDL-deficient families (10 -12), so that this protein is considered as a key for generation of HDL by the apolipoprotein-cell interaction and release of cellular cholesterol by this pathway.…”
mentioning
confidence: 99%